Induction of apoptosis via JNK and AKT/mTOR signaling pathways by Alternanthera sessilis (L.) R.Br. ex DC. in colorectal cancer in vitro and in vivo - Sivapragasam, Gothai (2019)
Incidence rates vary 10-fold globally for colorectal cancer (CRC). Asia has lower rates than Western countries, but as the Western life-style becomes more prevalent in economically developing Asian countries like Malaysia, rates are increasing. Dietary phytochemicals have been drawing increasing attention for CRC prevention and treatment due to their chemical diversity, biological activity, easy availability, lack of toxic effects, and ability to modulate various signal transduction pathways and cell processes. A. sessilis is a well-known medicinal perennial herb in traditional medicine it is used for different therapeutic purposes, such as venereal diseases, eye diseases, cancer and gastrointestinal related ailments. Despite its beneficial uses, no studies on its chemo-preventive potential have been reported. Thus, this study was designed to focus on the elucidation of the putative anticancer potential of A. sessilis extracts in-vitro human colorectal cells (HT-29) and in-vivo Sprague-Dawley (SD) rats by elucidating the effect of the extract on intermediate biomarkers which can be used as effective predictors of CRC. The preliminary in-vitro work examined the effects of extracts from three different plant parts (whole plant, leaf and stem) via cytotoxicity assay (MTT, colonogenic, cell motility and AOPI assay). All three plant extracts exhibited dose- and time-dependent killing capabilities in HT-29 cell line.Whole plant and leaf extract showed IC50 above 150 μg/mL, followed by 500 μg/mL for stem extract.The killing activity of A. sessilis leaf extract was more specific toward HT-29 cells, as the leaf extracts had reduced effect (IC50 >200 μg/mL) on healthy murine cells, 3T3 with higher cytotoxic potency on HT-29 cells. The bioactive composition profiling of A. sessilis leaf extract by GC-MS revealed presence of hexadecanoic acid, carbonic acid, octadecadienoic acid, linoleic acids, neophytadiene, phytol, heptadecanone, octadecyne, dodecanetetrol, decanoic acid and oxirane which is an essential medicinal compound owing properties such as anticancer, anti-inflammatory and antioxidant. The mechanism involved in the cytotoxic effect of the extract was then evaluated in terms of apoptosis by caspase -3, -8 and -9 colorimetric kit assay, mitochondrial membrane potential, cell cycle, Annexin V-FITC/PI staining, ROS and western blot analysis. The caspase assay data showed an increased level of all the tested caspase, MMP distruption was up to 70% in the highest concentration (200 μg/mL) when compared to control with only 2 %, cell cycle results indicate arrest in G2/M phase arrest, generation ROS was increased dose dependently, Anexin V FITC indicate that A. sessilis leaf extract successfully induce apoptosis in HT-29 cells with increased total apoptotic cells (16 %) compared to control group with only 2.8% and western blot analysis exhibited elevation of administration pro-apoptotic protiens with reduced anti-apoptotic protein upon treatment with A. sessilis leaf extract. In-vivo evaluation of azoxymethane (AOM)- induced CRC in SD rats assessing A. sessilis leaf extract efficacy, clinical assessment, histopathological and molecular studies were performed for pre-clinical colon cancer diagnosis. The results indicated that A. sessilis leaf extract oral and offered no side effects such as weight loss, behavior changes or changes in kidney, and liver functions were observed. These results may indicate that active doses of A. sessilis leaf extract are not toxic. Additionally, A. sessilis leaf extracts significantly inhibited colorectal carcinogenesis induced by AOM in SD rats by the reduction in the number of Abberant crypt Foci (ACF). The mechanistic studies demonstrate A. sessilis leaf extract strongly inhibits AOM induced CRC in SD rats by activating JNK signaling pathway via Akt inhibition. On the basis of these findings, A. sessilis leaf extract could be used to the development of new and efficient strategies for treatment of human CRC.